2008
DOI: 10.1373/clinchem.2007.100040
|View full text |Cite
|
Sign up to set email alerts
|

Immunodetection of Glycosylated NT-proBNP Circulating in Human Blood

Abstract: BACKGROUND:Brain natriuretic peptide (BNP) or NTproBNP (N-terminal fragment of BNP precursor) measurements are recommended as aids in diagnosis and prognosis of patients with heart failure. Recently it has been shown that proBNP is O-glycosylated in human blood. The goal of this study was to map sites on the NT-proBNP molecule that should be recognized by antibodies used in optimal NT-proBNP assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
117
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(127 citation statements)
references
References 9 publications
7
117
1
2
Order By: Relevance
“…ProBNP in nonprocessed form is found in healthy individuals and patients with HF (18 ). ProBNP is posttranslationally modified in patients with HF by O-glycosylation at several threonine and serine residues within the N-terminal region (amino acid residues 1-76), but not within the BNP-portion of proBNP (amino acid residues 77-108) (19 ). It appears that NTproBNP is glycosylated in the central region (amino acid residues 28 -56), while the C-terminus region of the molecule (amino acid residues 61-76) is not posttranslationally modified (19 ).…”
Section: Bnpmentioning
confidence: 99%
See 2 more Smart Citations
“…ProBNP in nonprocessed form is found in healthy individuals and patients with HF (18 ). ProBNP is posttranslationally modified in patients with HF by O-glycosylation at several threonine and serine residues within the N-terminal region (amino acid residues 1-76), but not within the BNP-portion of proBNP (amino acid residues 77-108) (19 ). It appears that NTproBNP is glycosylated in the central region (amino acid residues 28 -56), while the C-terminus region of the molecule (amino acid residues 61-76) is not posttranslationally modified (19 ).…”
Section: Bnpmentioning
confidence: 99%
“…ProBNP is posttranslationally modified in patients with HF by O-glycosylation at several threonine and serine residues within the N-terminal region (amino acid residues 1-76), but not within the BNP-portion of proBNP (amino acid residues 77-108) (19 ). It appears that NTproBNP is glycosylated in the central region (amino acid residues 28 -56), while the C-terminus region of the molecule (amino acid residues 61-76) is not posttranslationally modified (19 ). ProBNP, however, is glycosylated both in the central region and in the region located close to the cleavage site, specifically at amino acid residues 63-76.…”
Section: Bnpmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a recent study [34] suggested that the commercial immunoassays, commonly used for NTproBNP assay, employ non-glycosylated calibrator materials and mostly antibodies directed against epitopes with potential O-glycosylation site occupancy. Because the most part of circulating inactive peptides related to NT-proBNP and proBNP are O-glycosylated [7,18,35], these immunoassays cannot measure some glycosylated peptides [34,36]. Moreover, the commercially available immunoassays for NT-proBNP are interfered by the intact peptide proBNP (especially non-glycosylated peptide) [36] and also by some other shorter peptides derived from the proteolytic degradation of this pro-hormone [1] (Figure 2).…”
Section: Groupmentioning
confidence: 99%
“…In addition to the peptide hormone BNP and the inactive peptide NT-proBNP, a huge numbers of other circulating peptides derived from the pro-hormone proBNP can be identified by chromatographic procedures in human plasma, including the intact and glycosylated forms of proBNP itself [29][30][31][32][33]38] (Figure 2). Furthermore, the active hormone BNP may be produced even in vivo from the circulating intact precursor proBNP through enzymatic cleavage by some plasma proteases (such as corin) [35,36,39] (Figure 2). Indeed, a recent study, using an in vivo experimental rat model, demonstrated that the split of proBNP into BNP and NT-proBNP can actually occur in circulation [40].…”
Section: Quality Specifications For An Accurate Bnp Assaymentioning
confidence: 99%